Aspectos históricos da institucionalização da atenção à saúde do adolescente no estado de São Paulo, 1970-1990 Historical aspects of the institutionalization of adolescent healthcare in the state of São Paulo, 1970-1990 - Lígia Bruni Queiroz; José Ricardo de Carvalho Mesquita Ayres; Maria Ignez Saito; André Mota (História, Ciências, Saúde: Manguinhos)
Trata de aspectos históricos da atenção integral à saúde dos adolescentes no estado de São Paulo, sobretudo quanto à implantação de serviços e programas pioneiros. Contextualiza desafios, embates e dificuldades gerados no âmbito das instituições implicadas no desenvolvimento desse campo, à luz das perspectivas da medicina clínica e da saúde coletiva, tendo como pano de fundo o contexto sociopolítico brasileiro na época. Fundamentado em material documental, recupera-se a construção de núcleos de expertise e do campo da saúde do adolescente na dialética entre a construção de uma nova área de atuação médica com base na clínica e um campo de saberes e práticas da saúde coletiva com base na integralidade da atenção à saúde, de caráter interdisciplinar e intersetorial. The article explores historical aspects of integral healthcare for adolescents in the state of São Paulo, particularly in regard to the implementation of pioneering services and programs. Against the backdrop of Brazil's social and political context during this period, it contextualizes the challenges, clashes, and difficulties that arose within the institutions involved in developing this field, from the perspectives of clinical medicine and of collective health. Grounded on documental material, the study re-examines the construction of groups of expertise and of the field of adolescent health care as part of the dialectical interplay between the construction of a new area of medical practice based on clinical work and a field of knowledge and practices in collective health based on integral health care of an interdisciplinary, inter-sectoral nature.